Pengaruh Akuntansi Forensik dan Kemampuan Auditor Investigatif dalam Pengungkapan Kecurangan - Vita Citra Mulyandini; Frido Saritua Simatupang (Accounthink : Journal of Accounting and Finance, 2022)
The competence and ability of the auditor, especially if he is an investigator, is needed in detecting cases in Indonesia. Competence is education, knowledge, experience, and/or expertise, both on examination and on certain matters or fields. The abilities that must be possessed by an investigative auditor are basic knowledge of accounting, auditing, internal control, investigations and so on. Then the auditor must also have technical abilities such as understanding the law and legislation, be able to make hypotheses and collect evidence and investigative auditors have a mental attitude such as being independent and complying with standards. This research was conducted in all state-owned banks in Indonesia. Quantitative method in this study to examine the sample and analysis the established hypotheses. Descriptive quantitative was type of this research, which is researcher distributing questionnaires to all respondents then given a score. The data in this study is primary data directly obtained from the research location with the technique of distributing questionnaires. The population in this study were all BUMN Bank Auditors who conducted investigative audits. Sampling used in this research is purposive sampling.